Optimization of silver nanoparticles synthesis using Elaeis guineensis Jacq. residue extract and their antibacterial activity against Pseudomonas aeruginosa - Jorge Benjamín Diaz-López; Diana De la Cruz-Gumeta; Gabriela Alvarado-Arguello; Oscar Rico-Domínguez; Evelyn Valdez-Rodríguez; Karina Hernández-Ovalle; María Celina Luján-Hidalgo; Rosa Isela Cruz-Rodríguez; Rocío Meza-Gordillo (Journal of Materials Science: Materials in Engineering)
Abstract This study explores the green synthesis of silver nanoparticles (Ag NPs) using oil palm (Elaeis guineensis) residue as a reducing agent. The synthesis was optimized by analyzing the effects of pH, silver nitrate (AgNO3) concentration, and extract-to-AgNO3 ratios using a Taguchi L9 design. The highest yield theorist (72%) was achieved under the conditions of pH 10, 100 mM AgNO3 concentration, and a 2:3 extract-to-AgNO3 ratio. The synthesized Ag-NPs were characterized through UV–Vis (400–450 nm), Fourier-transform infrared spectroscopy (FT-IR, 1370 cm-1, attributed to the nitro group), dynamic light scattering (DLS, 10.07 nm average particle size with a hydrodynamic diameter (Dh) of 235.82 nm in a neutral pH), zeta potential (− 18.33 mV), scanning electron microscopy (SEM), and X-ray diffraction (XRD). Antimicrobial testing against Pseudomonas aeruginosa revealed antibacterial activity, making these nanoparticles a promising alternative to traditional antibiotics. Graphical Abstract